Zur Kenntnis der Tineidae von Slowenien (Lepidoptera) - Gaedike, Reinhard (Acta entomologica slovenica (Ljubljana), 2010)
The article presents a compilation of previously known information on the Tineidae of Slovenia and results of the examination of material, collected by the authors and numerous other collectors. 392 findings are listed from 125 locations for 44 species of the Slovenian Tineidae. We emphasize that Pelecystola fraudulentella (Zeller, 1852) was not found in Slovenia since 1850. Eight species are new to Slovenian fauna: Nemapogon inconditella (Lucas,1956), Nemapogon hungarica Gozmany, 1960, Nemapogon gliriella (Heyden, 1865), Agnathosia mendicella (Denis & Schiffermüller, 1775), Reisserita relicinella (Herrich-Schäffer, 1853), Infurcitinea finalis Gozmany, 1959, Tinea murariella Staudinger, 1859, Monopis crocicapitella (Clemens, 1859). Foreach species additional informations on the distribution and ecology are presented.
Keywords: entomologija; favna; metulji; najdbe; Slovenia; Slovenija